Quality improvement in anaesthesiology - Gupta, Maruti (International Journal of Research in Medical Sciences, 2019)
In recent times, numerous efforts have been made in the field of medicine to improve the methodology of measuring and reporting the quality of care delivered to patients. Most of these efforts have been executed in the western population, because of an efficient system of Incident Reporting. Quality Measurement in healthcare typically means quantifying processes of care that have a direct relationship to positive health outcomes. Quality in anaesthesia is usually measured by perioperative mortality, morbidity and Incidents. Quality measurement is not only important for the clientele but also for the employer, to make choices and healthcare provider to introspect his performance. It is an effective method of giving feedback to anaesthesiologists, doctors and paramedical staff to address quality issues and bring about improvement. Without Quality Measurement, improvement in quality, if at all, would be expected to be very slow and clientele would be blindfolded in taking important decisions pertaining to health care. The concepts of quality assurance and quality control are rapidly gaining popularity in surgical sciences as the society is heading towards social, technical and clinical advancements globally. In times to come, quality of anaesthesia services will be closely monitored by quality indicators and will become a benchmark for assessment of the healthcare provider and the hospital. At present, the need of the hour is to devise ways and means to measure the quality of care being provided by the healthcare provider and adopt these evolutionary practices aimed at improving anaesthesia delivery services in a medical setup.